Personality assessment results objectification of basic education program development - Trushnikov D. Y. (Pedagogical excellence and pedagogical technologies, 2016)
the article shows the experience of assessing the achievement of personal universal educational actions, the author's method, used in the implementation of quality assessment system of education in FAEI TD "Physical and Mathematical School", namely expert survey method using the developed in school "List of system analysis and evaluation of the didactic play efficiency".
Keywords: универсальные учебные действия; ФГОС; воспитание школьников; Universal educational actions; FSES; pupil upbringing